The formalization of organizational capabilities and learning: Results and challenges - Giovanni Dosi; Marco Faillo; Virginia Cecchini Manara; Luigi Marengo; Daniele Moschella (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2017)
This work offers an overview of recent formalizations of organizational capabilities and learning. We first present the main characteristics both of NK models and of the approach based on Classifier Systems, focusing on their early applications to organization studies. We then discuss how the use of these models has contributed, in the recent years, to the formal analysis of the development and change of firm's dynamic capabilities by improving our understanding of processes of organizational learning and adaptation, and of the relationship between cognitive and governance issues.
Keywords: D21; D23; D83; L23; 330; Capabilities; Decomposability; Organizational structure; Problem-solving